Efficient Multipath Routing and Anomaly Detection with a Token-Managed Certificateless Authentication Scheme (TM-AD) in WSNs (Informatica, 2025)
Wireless Sensor Networks (WSNs) are crucial for diverse Internet of Things (IoT) applications, but their inherent resource constraints and distributed nature expose them to significant security vulnerabilities. A primary challenge is the effective and timely detection and mitigation of malicious or misbehaving nodes, which can disrupt network operations, compromise data, and reduce network lifespan. Existing approaches often face obstacles in efficiently addressing these threats. This paper proposes the Token Manager-based Attack Detection (TM-AD) scheme, to enhance WSN security and operational efficiency. The TM-AD system features a "Token Manager" (TM), a dedicated entity responsible for continuous network monitoring, assessing node behavior based on defined parameters, and managing node participation through a token-based mechanism. Upon identifying malicious or anomalous activity, TM-AD facilitates uninterrupted network transmission by orchestrating the replacement of compromised nodes with designated "replacement nodes." The efficacy of the proposed TM-AD system is evaluated through comparative analysis. At 100 network nodes, TM-AD achieved a 100% attack detection rate and 100% network throughput, alongside a reduction in routing overhead of up to 43.8% and in end-to-end delay of up to 74.7% compared to benchmark schemes. These results affirm that TM-AD effectively identifies malicious nodes and significantly enhances network performance across these key metrics, thereby ensuring a more robust and reliable WSN operation.